2020
DOI: 10.21470/1678-9741-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity Index and Prognostic Nutritional Index in Predicting Atrial Fibrillation after On-Pump Coronary Artery Bypass Operations: a Prospective Study

Abstract: Introduction Rhythm problems are the most observed complications following coronary artery bypass grafting (CABG), the most common being postoperative atrial fibrillation (PoAF), with an incidence reaching 50% of the patients. In this study, we aimed to investigate the predictive importance of prognostic nutritional index (PNI) and visceral adiposity index (VAI) in predicting PoAF, which occurs after CABG accompanied by cardiopulmonary bypass. Methods Patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…(Fig. S3) In another cohort study, Engin et al (2020) showed that the visceral adiposity index significantly increased the risk of AF in patients who underwent isolated CABG.…”
Section: Waist Circumference Obesity Visceral Adiposity Index and Poafmentioning
confidence: 93%
See 1 more Smart Citation
“…(Fig. S3) In another cohort study, Engin et al (2020) showed that the visceral adiposity index significantly increased the risk of AF in patients who underwent isolated CABG.…”
Section: Waist Circumference Obesity Visceral Adiposity Index and Poafmentioning
confidence: 93%
“…Three studies (Engin et al, 2020;Girerd et al, 2009;Ivanovic et al, 2014) reported an analysis of the association between visceral adiposity and the risk of AF after CABG and included 536 cases among 2,691 participants. Due to the limited number of studies, we did not pool the results.…”
Section: Waist Circumference Obesity Visceral Adiposity Index and Poafmentioning
confidence: 99%
“…It has been shown that high BMI values can increase PoAF rates [ 5 ]. However, some studies revealed that central obesity may be a better predictor for PoAF [ 6 , 7 ]. Accordingly, waist/height ratio (WHR) is an important indicator of central obesity and it can be a better predictor than BMI in terms of the development of cardiovascular disease and impaired glucose tolerance [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These technological advances have also improved cardiopulmonary bypass (CPB) systems, and CABG operations can be performed with low mortality and morbidity rates. However, apart from mortality, morbid conditions such as renal failure, atrial fibrillation, and cerebrovascular accident may occur after these operations [2][3][4]. Postoperative atrial fibrillation (PoAF), one of these cases, can be seen at a rate of 25-40%.…”
Section: Introductionmentioning
confidence: 99%